Characteristics and factors associated with psychotic-like experiences in remission: a cross-sectional study of 4208 college students in China - Rui Wang; Yue Li; Meng Sun; Xin-Hu Yang; Liang Zhou; Hong-Ling Zhou (BMJ Open)
Objectives Previous research has extensively explored the factors associated with psychotic-like experiences (PLEs). However, the characteristics and associated factors of remitted PLEs, which refer to the absence of current PLEs following previous PLEs, remain unclear. Therefore, this study aims to describe the characteristics of adolescents who reported remitted PLEs.Design Cross-sectional study.Setting The survey was conducted from October to December 2020 in three colleges located in Guangzhou, China.Participants A total of 4208 college freshmen aged from 15 to 24 participated in our survey.Primary and secondary outcome measures The 15-item positive subscale of the Community Assessment of the Psychic Experience was used to assess both lifetime and current PLEs. Multivariate logistic regression models were used to examine the associations between remitted PLEs and a range of demographic factors, lifestyle, psychosocial factors, lifetime affective symptoms and sleep problems.Results Three groups of PLEs were observed: non-PLEs (47.27% of the sample), remitted PLEs (40.42%) and current PLEs (12.31%). Several factors have been identified as shared correlates of remission and absence of PLEs, including fewer recent adverse life events, greater resilience, fewer symptoms of depression and anxiety, and early waking. Furthermore, higher levels of social support (OR 1.48, 95% CI 1.01 to 2.17; OR 1.53, 95% CI 1.18 to 1.97) was a specific factor associated with the remission of PLEs. Compared with individuals without PLEs, those with remitted PLEs were more likely to be female (OR 1.50, 95% CI 1.28 to 1.75), less likely to be younger (OR 0.88, 95% CI 0.81 to 0.95) and prone to have more chronic physical illness (OR 1.67, 95% CI 1.29 to 2.16), habitual alcohol intake (OR 1.85, 95% CI 1.19 to 2.88), more childhood trauma (OR for low vs high=0.72, 95% CI 0.57 to 0.91) and the sleep problems of waking up easily (OR 1.36, 95% CI 1.12 to 1.65).Conclusion These findings suggest that remitted PLEs play a vital, unique role among three groups and provide preliminary targets for the intervention for adolescents at risk of mental health problems. Further investigation may shed light on the causality of the relationship between remitted PLEs and associated factors.